Uwarunkowania trwałości obecnego systemu władzy w Rosji - Świder, Konrad (Sprawy Międzynarodowe, 2018)
On March 18, 2018, on the fourth anniversary of the annexation of the Ukrainian Crimea, the incumbent President of the Russian Federation, Vladimir Putin, was elected for his fourth term – once again as the “non-alternative statesman”. This choice is a peculiar monument to the durability of the current system of power in Russia. This article analyzes various factors and mechanisms constituting the foundation of the current Kremlin team’s dominance in the political life of the Russian state. The process of consolidation of this elite in power began at the end of the 1990s – from the initiated by the administration of the previous Russian President Boris Yeltsin so-called project “Successor”. The next stage was the consolidation of power by the secret service corporation represented by the new Russian leader – Federal Security Service. The foundations of durability of this authority was also its economic, foreign and historical policy, as well as attempts by the Kremlin to create an integral state ideology based on the concept of sovereign democracy as a factor of social mobilization and the one of main sources of legitimacy of political domination in Russia.